ALTERITY IN THE BOOK OF DEDE KORKUT: THE IMAGE OF THE CHRISTIAN - Monire AKBARPOURAN (Fırat University, 2019)
Being one of the main tasks given to comparative literature, ‘Imagology’ or ‘the study of images’ is committed to, not only, expose the distance between the image of something or someone and reality, but also, to study the affinity that exists between the image of something or somebody and the conscience that has made this image exist. This distance and this affinity either change depending on the literary genre and context of the work. So we tend to forget them as time goes by and consequently we consider, sometimes an image as reality of that it is supposed to be a copy. In this way, the Christian image in The Book of Dede Korkut reflects certain historical facts while giving considerable space to imagination. In this article, we will study this image as well as the significance of the epic imaginary in its construction. From this point of view, the disbeliever, who is assigned the role of the foe of nomadic warriors, appears as a semi-imaginary creature created at a precise moment in history and in a specific context. This specific context – epic work –composed in honor of the holy war and the conquest of Anatolia does not give a realistic image of Turks either.